Factor p2 - 10p - 24.

Question

Asked 6/20/2013 1:03:40 PM

Updated 10/24/2014 7:53:12 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [10/24/2014 7:53:12 AM]

andrewpallarca|Points 22631|

andrewpallarca|Points 22631|

OxTornado007|Points 6879|

ibontxo|Points 356|

Question

Asked 6/20/2013 1:03:40 PM

Updated 10/24/2014 7:53:12 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by janezeshun [10/24/2014 7:53:12 AM]

Rating

0

The solution for x^2 - 4x - 3 = 0 is x = 7^1/2 + 2 , or x = -7^1/2 + 2 .

x^2 - 4x - 3 = 0

( x - 2 )^2 - 4 - 3 = 0

( x - 2 )^2 = 7

x - 2 = 7^1/2

x = 7^1/2 + 2

or

x - 2 = -7^1/2

x = -7^1/2 + 2

x^2 - 4x - 3 = 0

( x - 2 )^2 - 4 - 3 = 0

( x - 2 )^2 = 7

x - 2 = 7^1/2

x = 7^1/2 + 2

or

x - 2 = -7^1/2

x = -7^1/2 + 2

Added 10/24/2014 7:50:28 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [10/24/2014 12:12:49 PM]

0

p^2 - 10p - 24

= ( p - 12 ) ( p + 2 )

= ( p - 12 ) ( p + 2 )

Added 10/24/2014 7:51:43 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [10/24/2014 12:13:19 PM]

0

The center of the circle that has a diameter whose endpoints are (1, 3) and (-7, -1) is ( - 3 , 1 ) .

Let the center is ( x , y )

x = ( 1 - 7 ) / 2 = - 3

y = ( 3 - 1) / 2 = 1

Let the center is ( x , y )

x = ( 1 - 7 ) / 2 = - 3

y = ( 3 - 1) / 2 = 1

Added 10/24/2014 7:53:08 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [10/24/2014 12:14:41 PM]

Find the product.
2y 2(3x + 5z)
User: Find the product.
2y^2(3x + 5z)
User: Find the product.
-a 2b 2c 2(a + b - c)
**Weegy:** The answer is -8abc(a+b-c) **User:** Simplify (8m - 4n) + (6m + 3n).
**Weegy:** (8m - 4n) (6m 3n). What is the operation between 6m and 3n? **User:** Find the product.
a 4(3a 2 - 2a + 1)
**Weegy:** The answer for a^2 + 5a - 3a^2 is 5 a-2 a^2.
(More)

Question

Expert Answered

Updated 5/30/2014 9:01:57 AM

3 Answers/Comments

2y^2(3x + 5z) = 6xy^2 + 10y^2z

Added 5/30/2014 9:00:47 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:02:58 AM]

(8m - 4n) + (6m + 3n)

= 8m - 4n + 6m + 3n

= 14m - n

= 8m - 4n + 6m + 3n

= 14m - n

Added 5/30/2014 9:01:22 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:03:16 AM]

a^4(3a^2 - 2a + 1) = 3a^6 - 2a^5 + a^4

Added 5/30/2014 9:01:57 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/30/2014 9:03:34 AM]

The following sentence has a participle.
After an hour in the movie theater, the crying woman finally left to go blow her nose.
True
False **Weegy:** False. The sentence "After an hour in the movie theater, the crying woman finally left to go blow her nose." does not contain a participle. (More)

Question

Expert Answered

Updated 2/24/2014 2:11:19 PM

1 Answer/Comment

After an hour in the movie theater, the crying woman finally left to go blow her nose. It's TRUE that this sentence contains a participle: CRYING (that modifies the woman).

Added 2/24/2014 2:11:18 PM

This answer has been confirmed as correct and helpful.

After reading the sentence "The dog viciously attacked the young woman as she was walking down the sidewalk past the house," Breanna decided that viciously had a negative feeling. Breanna thought about the idiosyncrasies dialect signs connotation affix of the word. **Weegy:** I apologize, but I don't have a thorough understanding of what the question is asking. Would you mind re-writing it in order to express the question in relation to that statement? (More)

Question

Expert Answered

Updated 6/19/2013 10:26:50 AM

2 Answers/Comments

After reading the sentence "The dog viciously attacked the young woman as she was walking down the sidewalk past the house," Breanna decided that viciously had a negative feeling. Breanna thought about the CONNOTATION.

Added 6/19/2013 10:26:24 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [2/24/2014 2:10:28 PM]

If you can't answer a question, please pass it to another expert. Thanks!

Added 6/19/2013 10:26:50 AM

x2 + x - 12 = 0
**Weegy:** x2 - x - 90 = 0 in factored form is (x-10)(x+9)=0 (More)

Question

Expert Answered

Updated 9/11/2017 5:11:50 AM

1 Answer/Comment

(6 - d)(d^2 - 5 + 3d)

Question

Expert Answered

Updated 6/22/2016 12:23:48 PM

1 Answer/Comment

(6 - d)(d2 - 5 + 3d)

= 6d2 - 30 + 18d - d3 + 5d - 3d2

= - d3 + 3d2 + 23d - 30

= 6d2 - 30 + 18d - d3 + 5d - 3d2

= - d3 + 3d2 + 23d - 30

Added 6/22/2016 12:23:48 PM

This answer has been confirmed as correct and helpful.

27,363,626

questions answered

There are no comments.